Accepting the Other and Tolerance in the International Law of Human Rights - Al Fatlawi, Suhail Hussein (الجمعية العلمية للبحوث والدراسات الاستراتيجية, 2018)
The principle of accepting the other is an important element in the application of democracy and achieving peace and security between the members of the same society and establishing justice. People who refuse to accept the other cannot coexist with others, and hence wars erupt between them and consequently they suffer from the occurrence of catastrophes, disasters and tragedies, and all this due to their refusal to accept the other. In this research, we will discuss the principle of difference and diversity and the scope of difference and diversity and accepting the other, and we will end the research by a conclusion of most important results and suggestions.
Keywords: القانون الدولى -- حقوق الانسان -- التعايش السلمى -- القيم الانسانية